Mental Health Literacy Study of Tadulako University Students - Rasido, Ikhlas; Hasan, Hasan; Riyadi, Nur Eka Wahyuningsih (Bulletin of Counseling and Psychotherapy, 2025)
The preliminary study is an important, first step as a basis for intervention in improving the student’s mental health of the Faculty of Teacher Training and Education, Tadulako University. Previous research has confirmed students' mental health literacy based on gender, age, ethnicity, and education level. However, this research on determining risk groups based on differences in student mental health literacy between study programs is limited. The study aims to determine risk groups based on differences in Mental Health Literacy in 14 Programs Study of the Faculty of Teacher Training and Education, Tadulako University. The type of research used is a cross sectional study. The research procedure begins with distributing the Mental Health Literacy questionnaire to 730 new students in 14 Programs Study of the Faculty of Teacher Training and Education, Tadulako University. Academic Year 2024/2025 selected through quota sampling. Data analysis used descriptive statistics, and ANOVA. The findings are that the level of Mental Health Literacy of new students in 14 Programs Study of the Faculty of Teacher Training and Education, is in the category of Less by 43.43%, Sufficient by 49.18%, while only 7.12%, classified as Good, and 0.27% classified as Very Good. The vulnerable group of students' Mental Health Literacy is in the Undergraduate Program Study of Indonesian Language and Literature Education (p=0.39), Mathematics Education (p=0.227), History Education (p=0.330), Physics Education (p=0.10), and Guidance and Counseling (p=0.10). The results suggest interventions to improve student mental health literacy based on a priority scale in Programs Study that have student mental health literacy classified as vulnerable groups.